Furan fatty acid metabolite in newborns predicts risk of asthma. Issue 2 (27th October 2022) - Gürdeniz, Gözde; Kim, Min; Brustad, Nicklas; Ernst, Madeleine; Russo, Francesco; Stokholm, Jakob; Bønnelykke, Klaus; Hougaard, David; Rasmussen, Morten; Cohen, Arieh; Chawes, Bo
Abstract: Background: Intake of fish‐oil and fatty fish during pregnancy has been shown to reduce the risk of childhood asthma but biomarkers of such intake are lacking. Objective: To establish biomarkers of prenatal fish‐oil exposure from newborn dry blood spot metabolomics profiles and assess their relevance for childhood asthma risk stratification. Methods: The Danish COPSAC2010 mother–child cohort was utilized to investigate the effect of a double‐blinded randomized controlled trial of fish‐oil supplementation during pregnancy on dry blood spot liquid‐chromatography mass spectrometry‐based metabolomics profiles of 677 newborns. We thereafter investigated the association between fish‐oil associated biomarkers in the newborn and development of asthma‐related outcomes. Replication was sought in the independent observational COPSAC2000 cohort with 387 newborn metabolomics profiles. Results: The newborn metabolomics profiles differed between children in the fish‐oil vs. placebo group in COPSAC2010 (area under the receiver operator curve = 0.94 ± 0.03, p < .001). The fish‐oil metabolomics profile and the top biomarker, 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furan propanoic acid (CMPF) were both associated with a decreased risk of asthma by age 6 years (HR = 0.89, p = .002 and HR = 0.67, p = .005, respectively). In COPSAC2000, newborn CMPF level was also inversely associated with asthma risk by age 6 years (HR = 0.69, p = .01). Troublesome lung symptoms and common infections in the first 3 years were also inversely associated with newborn CMPF levels in both cohorts. Conclusions: Newborn children's blood levels of the furan fatty acid metabolite CMPF reflect fish‐oil and fatty fish intake during pregnancy and are associated with a lower risk of asthma across two cohorts, which could aid newborn screening for childhood asthma. Abstract : This study investigates the effect of fish‐oil supplementation during pregnancy on newborn dry blood spot metabolomics profiles in the COPSAC birth cohorts. The furan fatty acid metabolite CMPF was identified as top biomarker of the fish‐oil supplementation. Increasing newborn CMPF level was associated with decreased risk of infections and asthma in both cohorts. CMPF, 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furan propanoic acid; COPSAC, Copenhagen Prospective Studies of Asthma in Childhood; RTC, randomized controlled trial.Abbreviations: CMPF, 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furan propanoic acid; COPSAC, Copenhagen Prospective Studies of Asthma in Childhood; RTC, randomized controlled trial